Sequence variants of interleukin 6 (IL-6) are significantly associated with a decreased risk of late-onset Alzheimer's disease - Chen, Shih-Yuan (BioMed Central, 2012)
BACKGROUND: Interleukin 6 (IL-6) has been related to beta-amyloid aggregation and the appearance of hyperphosphorylated tau in Alzheimer's disease (AD) brain. However, previous studies relating IL-6 genetic polymorphisms to AD included few and unrepresentative single nucleotide polymorphisms (SNPs) and the results were inconsistent. METHODS: This is a case-control study. A total of 266 patients with AD, aged≧65, were recruited from three hospitals in Taiwan (2007-2010). Controls (n = 444) were recruited from routine health checkups and volunteers of the hospital during the same period of time. Three common IL-6 haplotype-tagging SNPs were selected to assess the association between IL-6 polymorphisms and the risk of late-onset AD (LOAD). RESULTS: Variant carriers of IL-6 rs1800796 and rs1524107 were significantly associated with a reduced risk of LOAD [(GG + GC vs. CC): adjusted odds ratio (AOR) = 0.64 and (CC + CT vs. TT): AOR = 0.60, respectively]. Haplotype CAT was associated with a decreased risk of LOAD (0 and 1 copy vs. 2 copies: AOR = 0.65, 95% CI = 0.44-0.95). These associations remained significant in ApoE e4 non-carriers only. Hypertension significantly modified the association between rs2069837 polymorphisms and the risk of LOAD (p(interaction )= 0.03). CONCLUSIONS: IL-6 polymorphisms are associated with reduced risk of LOAD, especially in ApoE e4 non-carriers. This study identified genetic markers for predicting LOAD in ApoE e4 non-carriers.